Cytogenetic studies in the redtail catfish, Phractocephalus hemioliopterus (Bloch & Schneider, 1801) (Siluriformes, Pimelodidae) a giant fish from Amazon basin - Swarça, Ana Claudia (2017)
Fil: Swarça, Ana Claudia. Universidad Estatal de Londrina. Centro de Ciencias Biológicas. Departamento de Histología; Brasil.